Evaluasi Pelaksanaan Urusan Administrasi Dalam Peningkatan Kompetensi Pada Departemen Otomotif Sekolah Menengah Kejuruan Negeri 2 Kota Palembang - Juliansyah, M. Fajri; Sakir, Icuk Muhammad; Iriani, Atrika (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2024)
This research aims to assess how administration is managed in an effort to increase competency in the Automotive Department at State Vocational High School 2, Palembang City. The method used is a qualitative method with a focus on case studies. Data was collected through interviews, observation and document examination. Research findings show that although administration in the Automotive Department is considered quite good, there are still several challenges such as a lack of adequate facilities and insufficient understanding of proper administrative procedures. In addition, there is a gap between the desired competency requirements and the reality of administrative implementation. Therefore, it is recommended that the Automotive Department at State Vocational School 2 Palembang City improve facilities, provide training on administrative procedures to staff, and carry out regular evaluations and improvements to increase administrative competence and efficiency.